The conditional relationship between renewable energy and environmental quality in Sub-Saharan Africa - Simplice Asongu; Chimere Okechukwu Iheonu; Kingsley O. Odo (African Governance and Development Institute (AGDI), 2019)
This paper complements existing literature by assessing the conditional relationship between renewable energy and environmental quality in a sample of 40 African countries for the period 2002 to 2017. The empirical evidence is based on fixed effects regressions and quantile fixed effects regressions. The findings from both estimation techniques show that renewable energy consistently decreases carbon dioxide (CO2) emissions. Moreover, the negative effect is a decreasing function of CO2 emissions or the negative effect of renewable energy on CO2 emissions decreases with increasing levels of CO2 emissions. In other words, countries with higher levels of CO2 emissions consistently experience a less negative effect compared to their counterparts with lower levels of CO2 emissions. Policy implications are discussed.
Keywords: Q32; Q40; Q45; O55; 330; Panel econometrics; Renewable energy; Carbon emissions; Africa